SM 01-2314 Catalyzing practice and research in the field of injury prevention: the division of analysis, research, and practice integration from 2013–2018 and the roadmap to 2023. (November 2018) - Qualters, Judy; Marr, Angela; Ballesteros, Michael; Mack, Karin
Abstract : The Division of Analysis, Research, and Practice Integration (DARPI) at the U.S. Centers for Disease Control and Prevention's Injury Center is taking stock of five years of research and practice. This session will start with a brief, high-level overview of accomplishments to date, but then turn more directly to new initiatives that will advance the field of injury prevention. DARPI seeks to actively catalyze systems change, as well as the translation and implementation of effective prevention strategies, to produce rapid, equitable, and sustainable reductions in injury and violence across communities. Presenters will explore DARPI's new initiatives in systems science, population level change, research-2-practice-2-reseach, data visualization, and statistical methods. For example, new projects are pushing forward the understanding of shared risk and protective factors that are associated with multiple injury and violence outcomes, the systems within they operate and other contextual factors that impact the adoption, implementation, and effectiveness of interventions in 'real-world settings'. Advances in data visualization of U.S. mortality data will be demonstrated, and the potential for new methodologies to better assess geospatial trends, identify aberrations that may signal an emerging problem, and forecast the impact of demographic, economic, and environmental changes on injury rates and outcomes will be discussed. DARPI's portfolio of activities is vast, yet targeted for maximum impact. Short and long-term objectives will be presented with the expectation for active dialogue to inform next steps. Our new initiatives embrace a partnership ecosystem to improve knowledge generation, incorporate expertise, and inspire collaborative innovation that tackles the most wicked injury and violence prevention problems.